Smoked tobacco dependence and its correlates among participants attending life skills training and counselling services programme across Karnataka (2017–2022) - Sonia Therat; Pradeep S. Banandur; Gautham M. Sukumar; Anusha B. Shenoy; Banavaram A. Arvind; Srividya Rudrapattana Nagaraja; Veeksha Rai; Upashana Medhi; Azad Devyani (Journal of Family Medicine and Primary Care)
Introduction: Indian National Mental Health Survey reports an alarming prevalence of 20.9% for tobacco dependence in India. Dependence on smoked tobacco can be prevented by thorough knowledge of the risk factors associated with it. Objectives: To estimate the prevalence and identify the factors associated with smoked tobacco dependence among participants attending the life skills training and counselling services programme (LSTCSP) across Karnataka from 2017 to 2022. Materials and Methods: Pretraining data of 3104 participants from training programmes between 2017 and 2022 were utilised. Univariate and multivariable logistic regression analysis was performed based on a conceptual framework with various hypothesised exposure variables and smoked tobacco dependence as outcome. Results: The overall prevalence of smoked tobacco dependence among LSTCSP participants who used smoked tobacco products was 59.4%. Ever use of smokeless tobacco products (Adjusted odds ratio (AOR) =2.05, 95% CI: 1.11–3.78) and screening positive for symptoms of generalised anxiety (AOR = 2.53, 95% CI: 1.32–4.84) significantly increased the odds of smoked tobacco dependence, whereas making decisions collectively in the family (AOR = 0.35, 95% CI: 0.18–0.66) and individuals with increased score for neurotic personality traits (AOR = 0.64, 95% CI: 0.44–0.93) were the factors associated with reduced odds of smoked tobacco dependence. Conclusion: The identified risk factors associated with smoked tobacco dependence are important to develop tobacco control programmes as well as in preventing its onset. With the risk factors for smoked tobacco dependence identified, the results of this study have implications for health promotion and prevention programmes as well as cessation programmes related to smoked tobacco dependence, within India and similar countries.